Science in a Review of Philosophy Related to Epistemology - Berlian Ocsis; Sofyan Sauri; Yoga Prima Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Knowledge is the result of human curiosity about something. Each type of knowledge also differs depending on how to obtain it and where to learn this knowledge. Talking about science, basically scientific activity in its development is due to three main problems, namely: what do you want to know, how to get knowledge, and what is the value of that knowledge. Epistemology includes the nature and sources of knowledge, methods of obtaining knowledge, and criteria for the validity of knowledge. The method used in this paper uses literature study methods or conducting studies from various books and other scientific works related to the topic raised, namely Science in Review of Philosophy Related to Epistemology: Definition and Scope of Epistemology, Theory of Truth, Objectivity of Science, and Methodology Science. This study aims to determine the extent to which the topic is related to current developments so as to produce new knowledge and contribute to knowledge that can be useful for the public.